2016
DOI: 10.5307/jbe.2016.41.2.108
|View full text |Cite
|
Sign up to set email alerts
|

Study of Radio Frequency Thawing for Cylindrical Pork Sirloin

Abstract: Purpose: Radio frequency (RF) heating is a promising thawing method, but it frequently causes undesirable problems such as non-uniform heating. This can occur because of the food shape, component distribution, and initial temperature differences between food parts. In this study, RF heating was applied to the thawing of cylindrically shaped pork sirloin by changing the shape of electrodes and the surrounding temperature. Methods: Curved electrodes were utilized to increase the thawing uniformity of cylindrical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Results indicated that radio frequency tempering led to a relatively uniform temperature distribution in lean meat, but resulted in a vastly large temperature difference in fat and lean meat blend. Kim et al () found that the edges and corners of cylindrical pork samples were over 20°C when to the center reached −4°C in a flat‐electrode radio frequency heating system. Curving the top flat electrode to fit the cylindrical pork sample could significantly improve the temperature uniformity.…”
Section: Introductionmentioning
confidence: 99%
“…Results indicated that radio frequency tempering led to a relatively uniform temperature distribution in lean meat, but resulted in a vastly large temperature difference in fat and lean meat blend. Kim et al () found that the edges and corners of cylindrical pork samples were over 20°C when to the center reached −4°C in a flat‐electrode radio frequency heating system. Curving the top flat electrode to fit the cylindrical pork sample could significantly improve the temperature uniformity.…”
Section: Introductionmentioning
confidence: 99%
“…A model of frozen pork, whose relative permittivity is ε ′=20.4, 5 and dielectric loss factors set to ε ″=8, 9,10 has a length and width fixed at 150 and 100 mm, respectively. The thickness' variation range is 20 to 100 mm (corresponding to a mass variation range of approximately 220 to 1200 g) is employed in the simulation.…”
Section: Simulations and Discussionmentioning
confidence: 99%
“…The operation frequency belongs to the ISM band, which can be used without application. 5,6 Moreover, the device which works in this frequency has an acceptable skin depth for frozen meat, so that the frozen meat can be heated rapidly and uniformly. Measurement results revealed that the thawing time was reduced from a maximum of about 8 hours to about 4 minutes compared with other three methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Llave et al [ 22 ] discovered the RF tempering rate of tuna fish was three times higher than that with air tempering and that the best uniformity occurred with a top electrode projection similar in size to the sample. Kim et al [ 23 ] investigated RF tempering of pork with a curved-shape top electrode and found that temperature uniformity was improved by using a top electrode with a projection area smaller than that of the sample. Koray Palazoğlu et al [ 24 ] compared RF (27.12 MHz) and microwave (915 MHz) tempering of frozen blocks of shrimp (1.75 kg) and observed that localized overheating occurred in samples subjected to microwave tempering.…”
Section: Introductionmentioning
confidence: 99%